Deanxit Combined with Cognitive Behavioral Therapy in Treating 31 Cases of Post-stroke Depression - Dujuan GE; Liyu WU; Sanfeng SUN; Lei SHANG; Qingjuan YANG; Xiaoru YANG; Qingxi ZHAO (康复学报)
Objective:To investigate the curative effects of Deanxit combined with cognitive behavioral therapy for the treatment of post-stroke depression.Methods:60 patients with post-stroke depression were randomly assigned to treatment group (n=30) and control group (n=30), the treatment group received Deanxit combined with cognitive behavioral therapy, and the control group received Deanxit only for two courses, four weeks as a course. The curative effect was assessed by Hamilton depression scale (HAMD), the neurologic function recovery was measured by national institutes of health stroke scale (NIHSS) and modified Barthel index (MBI), and the drug safety was evaluated by treatment emergent symptom scale (TESS).Results:After two courses, the total effective rate of the experimental group (93.5%) was higher than that of the control group (79.3%), and the difference was significant (P<0.05); after a course of treatment, the HAMD score in the two groups was decreased significantly compared with that before the treatment (P<0.01); the weekly score in the treatment group was lower than that of the control group, and the difference was significant at the first weekend and the second weekend (P<0.05, P<0.01). After treatment of one week, two weeks, four weeks and eight weeks, the NIHSS score in the two groups was respectively decreased, and MBI score was respectively increased compared with that before treatment; the NIHSS score in the treatment group was lower than that of the control group, the MBI score was higher than that of the control group, and the difference was significant after treatment of one week, four weeks and eight weeks (P<0.05, P<0.01). No obvious adverse reactions appeared in the two groups during the treatment process.Conclusion:Deanxit combined with cognitive behavior therapy has good efficacy and safety for post-stroke depression.